Rotary ultrasonic assisted machining of mould and die material - Raja Abdullah, Raja Izamshah; Ramli, Azlan; Kasim, Mohd Shahir; Mohd Zakaria, Muhammad Akmal; Ding, Song Lin (Penerbit UTeM, 2019)
The high strength properties of hardened steel AISI D2 material (~51 HRc) have created problems to the conventional machining process; poor machined surface, high cutting force, extreme machining temperature and rapid tool wear. In order to solve the discrepancies in machining the material, this paper proposed a hybrid machining process technique that combined a high frequency ultrasonic vibration (~20 kHz) with the rotating end mill. An in-house ultrasonic tool holder that fitted the CNC machine spindle was developed to perform the ultrasonic assisted machining process. A set of experimental work was conducted to evaluate the improvement of the ultrasonic vibration in the cutting process. The evaluation included the effects of machining parameter namely cutting speed, feed rate, depth of cut, ultrasonic frequency and vibration amplitude in improving the surface roughness value for machining hardened AISI D2 material. The analytical results demonstrated that the presence of the ultrasonic vibration was able to improve the machined surface roughness in that up to 80% reduction in Ra value was observed as compared to the conventional machining process within the same cutting conditions.